CRISPR/Cas9-mediated gene knockout reveals a guardian role of NF-κB/RelA in maintaining the homeostasis of human vascular cells. Issue 11 (2nd July 2018) - Wang, Ping; Liu, Zunpeng; Zhang, Xiaoqian; Li, Jingyi; Sun, Liang; Ju, Zhenyu; Li, Jian; Chan, Piu; Liu, Guang-Hui; Zhang, Weiqi; Song, Moshi; Qu, Jing
Abstract: Vascular cell functionality is critical to blood vessel homeostasis. Constitutive NF-κB activation in vascular cells results in chronic vascular inflammation, leading to various cardiovascular diseases. However, how NF-κB regulates human blood vessel homeostasis remains largely elusive. Here, using CRISPR/Cas9-mediated gene editing, we generated RelA knockout human embryonic stem cells (hESCs) and differentiated them into various vascular cell derivatives to study how NF-κB modulates human vascular cells under basal and inflammatory conditions. Multi-dimensional phenotypic assessments and transcriptomic analyses revealed that RelA deficiency affected vascular cells via modulating inflammation, survival, vasculogenesis, cell differentiation and extracellular matrix organization in a cell type-specific manner under basal condition, and that RelA protected vascular cells against apoptosis and modulated vascular inflammatory response upon tumor necrosis factor α (TNFα) stimulation. Lastly, further evaluation of gene expression patterns in IκB α knockout vascular cells demonstrated that IκBα acted largely independent of RelA signaling. Taken together, our data reveal a protective role of NF-κB/RelA in modulating human blood vessel homeostasis and map the human vascular transcriptomic landscapes for the discovery of novel therapeutic targets.